2005
DOI: 10.1108/14601060510627830
|View full text |Cite
|
Sign up to set email alerts
|

The validation of a use innovativeness scale

Abstract: Purpose -To validate a measure of use innovativeness, or how existing products are used in a novel and innovative manner. The measure has practical significance for innovation research as it consists of only nine items as opposed to the original 44. The use innovativeness measure derived from research predicts acceptance of new technology (in this case computer technology) and could be adapted to other fields of innovation research. Design/methodology/approach -A survey was conducted and structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 14 publications
(10 reference statements)
3
30
0
7
Order By: Relevance
“…On the subject of innovativeness, Girardi et al (2005) suggests that innovating organizations search for opportunities, accept risks, pursue financial profits and organize resources, while, as a group, representing the possibilities for change in their societies. A clear consensus in the literature about the influence of the innovation indicates its relevance to economic performance in both organizations and countries (Paladino, 2008).…”
Section: Business Achievementsmentioning
confidence: 99%
“…On the subject of innovativeness, Girardi et al (2005) suggests that innovating organizations search for opportunities, accept risks, pursue financial profits and organize resources, while, as a group, representing the possibilities for change in their societies. A clear consensus in the literature about the influence of the innovation indicates its relevance to economic performance in both organizations and countries (Paladino, 2008).…”
Section: Business Achievementsmentioning
confidence: 99%
“…Thus, opinion leaders' primary goal is to deliberately influence other consumers (and their purchase behavior), which sets them apart from innovators. Opinion seekers illustratively do not want to be unique (Bertrandias & Goldsmith, 2006), pay high value to their social consent (Bertrandias & Goldsmith, 2006), and are inversely related to innovativeness, which means that opinion leaders are highly innovative but their innovativeness influences opinion seekers as well (Girardi, Soutar & Ward, 2005). Ruvio & Shoham (2007) significantly grounded the existence of these differences between opinion leaders and opinion seekers.…”
Section: Opinion Leaders (Innovatism)mentioning
confidence: 99%
“…According to previous researches the variables product knowledge, product usage and product involvement as the moderator variables, affect the domain-specific innovativeness in the consumer innovativeness hierarchy model (Girardi, Soutar, & Ward, 2005;Goldsmith, Hauteville, & Flynn, 1998;Grewal, Mehta, & Kardes, 2000) so it is suggested that this subject will be investigated in future researches.…”
Section: Suggestions For Future Researchesmentioning
confidence: 99%